Inherited non-invertible duality symmetries in quiver SCFTs - Argurio, Riccardo; Collinucci, Andrés; Mancani, Salvo; Meynet, Shani; Mol, Louan; Tatitscheff, Valdo (Journal of high energy physics, 2025)
We revisit the construction of the duality group for N = 2̂ An-shaped quivers SCFTs and generalize it to the previously unexplored case of̂ Dn-shaped quivers. We then provide a systematic description of non-invertible duality symmetries in both classes. Furthermore, we characterize the N = 1 mass deformations of these theories that preserve such symmetries, thereby identifying a large class of N = 1 SCFTs with non-invertible dualitysymmetries inherited from their parent N = 2 theories.
Veröffentlicht: 24. Juni 2025
Gesehen am 10.11.2025